Shifting Patterns of Religious Literacy among University Students: A Study of Islamic Identity Formation in Indonesian Higher Education - Husni, Husni; Sahal, Yosep Farhan Dafik (Bestari, 2025)
This article investigates emerging patterns of religious literacy and Islamic identity formation among university students in Indonesia, particularly within public and Islamic higher education institutions. Through mixed-methods research involving surveys, focus group discussions, and document analysis, the study identifies a significant shift in students’ modes of engaging with Islamic knowledge—from conventional textual study to digital platforms such as social media, online preachers, and algorithm-driven content. The findings reveal variations in students’ interpretive frameworks, ranging from textual-literal to contextual-progressive orientations, influenced by digital ecosystems and campus environments. While online access has democratized religious learning, it has also created fragmented understanding and susceptibility to polarized discourses. The study argues that universities must redesign Islamic education programs to strengthen critical digital literacy, foster dialogical engagement, and cultivate balanced Islamic worldviews. By analyzing how young Indonesians negotiate personal faith, social identity, and mediated religious authorities, this research offers insights into the dynamic landscape of contemporary Islamic religiosity in Southeast Asia.